Factors Associated With Choice of Web or Print Intervention Materials in the Healthy Directions 2 Study. (February 2014) - Greaney, Mary L.; Puleo, Elaine; Bennett, Gary G.; Haines, Jess; Viswanath, K.; Gillman, Matthew W.; Sprunck-Harrild, Kim; Coeling, Molly; Rusinak, Donna; Emmons, Karen M.
Background . Many U.S. adults have multiple behavioral risk factors, and effective, scalable interventions are needed to promote population-level health. In the health care setting, interventions are often provided in print, although accessible to nearly everyone, are brief (e.g., pamphlets), are not interactive, and can require some logistics around distribution. Web-based interventions offer more interactivity but may not be accessible to all. Healthy Directions 2 was a primary care–based cluster randomized controlled trial designed to improve five behavioral cancer risk factors among a diverse sample of adults ( n = 2, 440) in metropolitan Boston. Intervention materials were available via print or the web. Purpose . To (a) describe the Healthy Directions 2 study design and (b) identify baseline factors associated with whether participants opted for print or web-based materials. Methods . Hierarchical regression models corrected for clustering by physician were built to examine factors associated with choice of intervention modality. Results . At baseline, just 4.0% of participants met all behavioral recommendations. Nearly equivalent numbers of intervention participants opted for print and web-based materials (44.6% vs. 55.4%). Participants choosing web-based materials were younger, and reported having a better financial status, better perceived health, greater computer comfort, and more frequent Internet use ( p < .05) than those opting for print. In addition, Whites were more likely to pick web-based material than Black participants. Conclusions . Interventions addressing multiple behaviors are needed in the primary care setting, but they should be available in web and print formats as nearly equal number of participants chose each option, and there are significant differences in the population groups using each modality.